Beginning Android 3 - Murphy, Mark (Apress : Imprint: Apress, 2011)
The vibrant and rich Android development platform, created by Google and the Open Handset Alliance, continues to be a platform in its truest sense, encompassing hundreds of classes beyond the traditional Java classes and open source components that ship with the software development kit. Android's continued growth includes support for Flash and Flash gaming apps, Wi-Fi tethering, improved performance, WebM or WebMedia integration for HTML5-based video and other multimedia APIs, Chrome OS (WebOS) integration, and more. With Beginning Android 3, you'll learn how to develop applications for Android 3 mobile devices using simple examples that are ready to run with your copy of the software development kit. Author, Android columnist, developer, and community advocate Mark L. Murphy will show you what you need to know to get started programming Android applications, including how to craft graphical user interfaces, use GPS, multi-touch, multi-tasking, and access web services.